Building Resilience Intervention (BRI) with teachers in Bedouin communities: From evidence informed to evidence based. (April 2018) - Baum, Naomi L.; Stokar, Yaffa N.; Ginat-Frolich, Rivkah; Ziv, Yuval; Abu-Jufar, Ibrahim; Cardozo, Barbara Lopes; Pat-Horenczyk, Ruth; Brom, Danny
Abstract: The Building Resilience Intervention (BRI), a program developed in the wake of terrorism and war in Israel, provides teachers with resilience-building skills that enable them to support students suffering from post-traumatic distress. Teachers in the Bedouin city of Rahat were evaluated both before and after the BRI workshop intervention for post-traumatic distress levels, functional impairment, flexibility, emotional regulation, general resilience measures and workshop impact. Results showed significant increases among teachers in areas such as positive refocusing and reappraisal, and increased willingness to discuss traumatic material with their students. Incorporating resilience training in teacher education is discussed. Highlights: Teachers participated in building resilience workshops and evidenced change. Teachers showed significant increases in resilience, coping and emotional regulation. Teachers reported increased levels of knowledge, skills and resilience behavior in the classroom. Teachers reported high levels of satisfaction from the BRI workshops. Training in resilience prepares teachers for challenges they will face in the class.